Breaking barriers and building bridges : an appraisal of the missionary legacy in India : 20th anniversary commemorative issue of Dharma Deepika: a South Asian journal of missiological research (1995-2015) - Kalapati, Joshua; Jeyaraj, Daniel; Gabriel, Merigala; Hedlund, Roger E.; Hedlund, June (Chennai, TN,India. Mylapore Institute for Indigenous Studies(MIIS), Inter Church Service Association(ICSA), 2016)
Contributed articles.
"The Dharma Deepika, 20th anniversary special commemorative volume released as a festschrift in honour of Roger and June Hedlund"--Cover.
Includes bibliographical references and index.
Keywords: Missions; Missions -- India; Church History.-- India